1992
DOI: 10.1007/bf00319008
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and performance of the aspen blotch miner, Phyllonorycter salicifoliella, on three host-tree species

Abstract: Larvae of the aspen blotch miner, Phyllonorycter salicifoliella Chambers (Lepidoptera: Gracillariidae), feed within leaves of three host-tree species in north-central Minnesota, USA. Far more individuals occur on Populus tremuloides than on P. balsamifera or P. grandidentata. We tested whether this pattern of host use reflected variable performance among alternative hosts by examining survivorship, sources of mortality, pupal mass, feeding efficiency, and development time of miners on each tree species. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Egg densities on Populus sieboldii and S. hultenii were much higher than those on S. sachalinensis and S. miyabeana despite good survival on S. miyabeana and no survival on S. hultenii. Poor correlation between egg density and larval performance in the field agrees with the results of several studies of other leaf miners (Valladares and Lawton 1991;Auerbach and Alberts 1992;Koricheva and Haukioja 1994). One hypothesis to explain the poor correlation is that expected larval performance was considerably reduced by density-dependent mortality factors; this occurs because larvae on more-favored plants tend to reach high density and are more likely to suffer from density-dependent mortality.…”
Section: Preference and Performance Linkagesupporting
confidence: 76%
See 2 more Smart Citations
“…Egg densities on Populus sieboldii and S. hultenii were much higher than those on S. sachalinensis and S. miyabeana despite good survival on S. miyabeana and no survival on S. hultenii. Poor correlation between egg density and larval performance in the field agrees with the results of several studies of other leaf miners (Valladares and Lawton 1991;Auerbach and Alberts 1992;Koricheva and Haukioja 1994). One hypothesis to explain the poor correlation is that expected larval performance was considerably reduced by density-dependent mortality factors; this occurs because larvae on more-favored plants tend to reach high density and are more likely to suffer from density-dependent mortality.…”
Section: Preference and Performance Linkagesupporting
confidence: 76%
“…In contrast to laboratory conditions, oviposition behavior may be affected by several environmental factors in the field. In this context, some studies have suggested that oviposition behavior was affected by difference in plant phenology (Auerbach and Alberts 1992), relative abundance of preferred host plants (Rausher 1980), or distribution of nonhost plants (Tahvanainen and Root 1972;Kareiva 1983;Visser 1986). For example, the butterfly Euphydryas chalcedona lays eggs on a less-preferred but easily accessible plant when a more-preferred plant is rare (Williams 1983;Williams et al 1983).…”
Section: Preference and Performance Linkagementioning
confidence: 99%
See 1 more Smart Citation
“…We combined all eulophid parasitism, since species could not be reliably distinguished as larvae or from pupal cases at the time of dissection. There was evidence of host feeding predation (larval predation), indicated by a collapsed and empty skin of the sap-feeding-stage larva attached to the lower mine surface (Jervis and Kidd 1986;Auerbach and Alberts 1992). Host feeding predation on Phyllonorycter is usually attributed to eulophids (Van Dreische and Taub 1983; Barrett and Jorgensen 1986).…”
Section: Methodsmentioning
confidence: 97%
“…During dissection of Phyllonorycter mines, causes of mortality are usually easy to determine (Pottinger and LeRoux 1971;Auerbach and Alberts 1992;Fritz and Kaufman 1993). At the time collections were made (August), most surviving Phyllonorycter had pupated and emerged.…”
Section: Methodsmentioning
confidence: 99%